§ 1.

      11. f(x).
f(x) 0 = , :

11.01.

f(x) = 3x5 2x4 x3 + 2x2 4x + 6, x0 = 3;

11.02.

f(x) = 2x6 x4 + 3x2   x 8, x0 = 2;

11.03.

f(x)= 4x4 4x+ 3x2 2x + 6, x0 = 3;

11.04.

f(x)= 3x6 2x4 + 3x3 4x + 1, x0 = 2;

11.05.

f(x) = 2x5 3x4 4x3 + x2 x 2, x0 = 2;

11.06.

f(x)= 4x5 2x3 2x2 + 4x + 6, x0 = 3;

11.07.

f(x)= 4x6 x5 + x4 3x2 + 2x 1, x0 = 4;

11.08.

f(x) = 5x4 4x3 3x+ x 6, x0 = 4;

11.09.

f(x) = 3x6 2x3 4x+ 3x 4, x0 = 2;

11.10.

f(x) = 3x6 2x5 4x3 2x + 8, x0 = 4;

11.11.

f(x)= 2x6 3x5 + 2x4 x3 2x + 6, x0 = 3;

11.12.

f(x)= 3x5 4x3 + 2x2 4x + 6, x0 = 3;

11.13.

f(x)= 4x6 3x5 2x4 3x + 5, x0 = 2;

11.14.

f(x) = 3x6 2x5 + 8x2 4x 3, x0 = 2;

11.15.

f(x) = 5x4 4x3 + 3x2 2x + 19, x0 = 4;

11.16.

f(x) = 3x5 2x4 3x2 + x 7, x0 = 2;

11.17.

f(x) = 6x7 3x5 2x4 + x3 4, x0 = 1;

11.18.

f(x) = 7x6 5x5 4x3 + 2x2 2x + 8, x0 = 1;

11.19.

f(x) = 5x7 4x4 + 3x2 + 6x + 4, x0 = 1;

11.20.

f(x) = 6x7 4x4 3x3 + 4x2 6x 3, x0 = 1;

11.21.

f(x) = 3x4 4x3 + 8x2 6x + 18, x0 = 2;

11.22.

f(x) = 3x5 4x3 + 2x2 3x 20, x0 = 2;

11.23.

f(x) = 2x5 4x3 + 6x2 7x + 19, x0 = 1;

11.24.

f(x) = 3x6 2x5 x4 3x2 + 6, x0 = 1;

11.25.

f(x) = 7x6 2x4 3x2 + 2x 18, x0 = 1;

11.26.

f(x)= 2x4 3x3 + 6x2 8x + 6, x0 = 3;

11.27.

f(x)= 3x4 2x3 5x2 + 6x 18, x0 = 3;

11.28.

f(x)= 5x4 + 2x3 6x2 x 7, x0 = 4;

11.29.

f(x) = 2x6 3x5 4x2 3x + 1, x0 = 4;

11.30.

f(x) = 2x6 3x5 + 7x2 + x 21, x0 = 2;

11.31.

f(x) = 8x5 3x3 2x2 + 6x + 2, x0 = 1;

11.32.

f(x)= 3x6 x5 + 2x4 + 3x 10, x0 = 2;

11.33.

f(x)= 4x6 2x4 + 3x3 6x + 18, x0 = 2;

11.34.

f(x)= 7x5 2x3 4x2 + 8x 21, x0 = 1;

11.35.

f(x)= 4x7 2x6 + x 2x2 + 6x 10, x0 = 1;

11.36.

f(x)= 7x5 6x4 + x3 12x2 + x 20, x0 = 4.

\..\

                              Copyright © 2008-2009 ..   . .